Masculinity, asceticism, Hinduism : past and present imagining of India - Chakraborty, Chandrima (Permanent Black ; Distributed by Orient Blackswan, 2011)
Studies on the works of Bankim Chandra Chatterji, Rabindranath Tagore, and Mahatma Gandhi.